Differential Metabolites Markers from Trunking and Stressed Non-Trunking Sago Palm (Metroxylon sagu Rottb.) - Hasnain, Hussain; Yan, Wei Jie; Zainab, Ngaini; Norzainizul, Julaihi; Rina, Tommy; Showkat, Ahmad Bhawani (Bentham Science Publishers, 2020)
Background: Sago palm is an important agricultural starch-producing crop in Malaysia. The trunk of sago palm is responsible for the production of the starch reaching maturity for harvesting after ten years. However, there are sago palms that failed to develop its trunk after 17 years being planted. This is known as a stressed “non-trunking” sago palm, which eliminates the economic value of the palms.